Peran Komunikasi Interpersonal dalam Penyebaran Teknologi Green House di Sanggar Kegiatan Belajar Situbondo - Sylva Alkornia (Kanal: Jurnal Ilmu Komunikasi, 2017)
The process of disseminating greenhouse technology in the Learning Activity Center (SKB) Situbondo a lot obstacles in its implementation. The purpose of this research analyzed the development of green house in SKB Situbondo as center of empowerment of manggo farmer. This research was done in SKB Situbondo which is location of spread of green house technology. This research used qualitative descriptive study. Data were collected by interview, observation, and literature study. The research data was validated by using source triangulation. Data analysis technique used interactive analysis model. The result of the research showed that (1) the conflict between mango farmers and SKB Situbondo was due to differences of views between the two parties, (2) the distribution was done to solve the problems faced by mango farmers after the harvest season ends with the learning guard as mediator, and (3) interpersonal communication running effectively where the terms of communication effectiveness had been met: openness, empathy, supportive attitude, positive attitude, and equality. The fulfillment of these five requirements, interpersonal communication had been running and expected to achieve its goal, change the attitude and behavior of mango farmers.